A Blockchain Model for Secure Communications in Internet of Vehicles - Mershad, Khaleel (2021)
The wide expansion of the Internet of Things is pushing the growth of vehicular ad-hoc networks (VANETs) into the Internet of Vehicles (IoV). Secure data communication is vital to the success and stability of the IoV and should be integrated into its various operations and aspects. In this paper, we present a framework for secure IoV communications by utilizing the High Performance Blockchain Consensus (HPBC) algorithm. Based on a previously published communication model for VANETs that uses an efficient routing protocol for transmitting packets between vehicles, we describe in this paper how to integrate a blockchain model on top of the IoV communications system. We illustrate the method that we used to implement HPBC within the IoV nodes. In order to prove the efficiency of the proposed model, we carry out extensive simulations that test the proposed model and study its overhead on the IoV network. The simulation results demonstrated the good performance of the HPBC algorithm when implemented within the IoV environment.